2004
DOI: 10.1038/sj.onc.1207599
|View full text |Cite
|
Sign up to set email alerts
|

PTEN can inhibit in vitro organotypic and in vivo orthotopic invasion of human bladder cancer cells even in the absence of its lipid phosphatase activity

Abstract: Recent studies have found a higher frequency of the PTEN tumor-suppressor gene alterations in invasive bladder carcinoma than in superficial disease, suggesting that PTEN is important in this process. A role of PTEN in bladder cancer invasion is further suggested by the fact that PTEN is a regulator of cell motility, a necessary component of tumor invasion. However, it is unknown whether PTEN is mechanistically involved in 'in vivo' tumor invasion or merely an epiphenomenon and, if the former is true, whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…As with other solid tumors, the activation of oncogenes and the abnormal expression of tumor suppressor genes are considered the main reasons for the occurrence of osteosarcoma (18). Previous studies have revealed that PTEN inhibits the proliferation, invasion and metastasis of tumor cells (19)(20)(21). The mutation and deletion of the PTEN gene have been confirmed to occur in osteosarcoma in dogs, where, in 60% of osteosarcoma cells, PTEN gene expression was suppressed or the gene was deleted (22).…”
Section: Discussionmentioning
confidence: 99%
“…As with other solid tumors, the activation of oncogenes and the abnormal expression of tumor suppressor genes are considered the main reasons for the occurrence of osteosarcoma (18). Previous studies have revealed that PTEN inhibits the proliferation, invasion and metastasis of tumor cells (19)(20)(21). The mutation and deletion of the PTEN gene have been confirmed to occur in osteosarcoma in dogs, where, in 60% of osteosarcoma cells, PTEN gene expression was suppressed or the gene was deleted (22).…”
Section: Discussionmentioning
confidence: 99%
“…The role of PTEN in negatively regulating cell migration is probably the reason why PTEN can suppress tumor invasion and metastasis. Indeed, in a human bladder cancer cell line with a functionally impaired PTEN, it was found that transfection of wild-type PTEN inhibited both soft agar colony formation and cancer cell invasion, whereas transfection of the G129E mutant inhibited cancer cell invasion but failed to suppress colony formation, indicating a role for lipid phosphatase activity and protein phosphatase activity in inhibiting cell growth and cell migration, respectively [20]. The putative protein phosphatase activity of PTEN might also regulate the cell cycle, because the G129E mutant retains the capability to arrest cell cycle of MCF-7 cells as wildtype PTEN, while the G129R and H123Y mutants (they lack both phosphatase activities as the C124S mutant) do not [21].…”
Section: Pten As a Tumor Suppressor And Master Cellular Regulatormentioning
confidence: 99%
“…10,11,14 Six-week-old nude mice were purchased from National Cancer Institute (Bethesda, MD) and were maintained under University of Virginia Animal Care and Use Committee guidelines. To generate cell lines with propensity for liver metastasis, mice were injected with 1 ϫ 10 6 T24T cells in 100 l of serum-free Dulbecco's modified Eagle's medium into the splenic capsule.…”
Section: Derivation Of Metastatic Cell Lines and Crossed Site Experimmentioning
confidence: 99%